ETHICS AND LAW OF HEALTH WORKERS IN MEDICAL SERVICE PRACTICE - Harold Rifano Masharto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This paper examines the ethics and law of health workers in medical service practices and the sanctions or legal basis applied if negligence occurs in medical service practices. Ethics and law are two important components in health worker practice. In the context of medical services, health workers are not only technically and professionally responsible, but must also comply with applicable ethical principles and legal norms. This article analyzes the relationship between professional ethics and law in the responsibilities of health workers, both in providing services, making medical decisions, and being accountable for errors or negligence that occur. The approach used is normative and empirical juridical with literature studies. It was found that harmonization between ethical and legal rules can prevent conflicts between patients and medical personnel and improve the quality of health services.